Comparison Between Individually and Group-Based Insulin Pump Initiation by Time-Driven Activity-Based Costing. (July 2017) - Ridderstråle, Martin
Background: Depending on available resources, competencies, and pedagogic preference, initiation of insulin pump therapy can be performed on either an individual or a group basis. Here we compared the two models with respect to resources used. Methods: Time-driven activity-based costing (TDABC) was used to compare initiating insulin pump treatment in groups (GT) to individual treatment (IT). Activities and cost drivers were identified, timed, or estimated at location. Medical quality and patient satisfaction were assumed to be noninferior and were not measured. Results: GT was about 30% less time-consuming and 17% less cost driving per patient and activity compared to IT. As a batch driver (16 patients in one group) GT produced an upward jigsaw-shaped accumulative cost curve compared to the incremental increase incurred by IT. Taking the alternate cost for those not attending into account, and realizing the cost of opportunity gained, suggested that GT was cost neutral already when 5 of 16 patients attended, and that a second group could be initiated at no additional cost as the attendance rate reached 15:1. Conclusions: We found TDABC to be effective in comparing treatment alternatives, improving cost control and decision making. Everything else being equal, if the setup is available, our data suggest that initiating insulin pump treatment in groups is far more cost effective than on an individual basis and that TDABC may be used to find the balance point.